2012
DOI: 10.1002/zaac.201200318
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rhenium‐Doped MoS2 Nanoparticles with Fullerene‐Like Structure

Abstract: The synthesis of rhenium‐doped fullerene‐like MoS2 nanoparticles (Re:IF‐MoS2) is described. Careful inductively coupled plasma mass spectrometry analysis reveals that the concentration of the rhenium atoms in the IF‐MoS2 lattice is more than 10‐fold smaller than the weighted amount of this atom in the precursor powder. High resolution scanning transmission electron microscopy in high angle annular dark field mode is used to decipher the isolated rhenium atoms in the MoS2 lattice and confirm that these atoms su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
(16 reference statements)
3
29
0
Order By: Relevance
“…This is not surprising as ZDDP forms thick tribofilms that prevent 7,9) surfaces from wearing. It is interesting to note that all three nanoparticles investigated in this study showed lower disc wear than PAO with ZDDP.…”
Section: Friction and Wearmentioning
confidence: 87%
See 4 more Smart Citations
“…This is not surprising as ZDDP forms thick tribofilms that prevent 7,9) surfaces from wearing. It is interesting to note that all three nanoparticles investigated in this study showed lower disc wear than PAO with ZDDP.…”
Section: Friction and Wearmentioning
confidence: 87%
“…The concentration of Re in the Re/IF-MoS 2 is about 100 ppm (0.01 at.%). A detailed description about the synthesis can be found elsewhere [9]. The size of the IF-MoS 2 is approximately 120-130 nm (mean value) in diameter.…”
Section: Lubricants and Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations